2020
DOI: 10.1002/alr.22669
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental black carbon exacerbates nasal epithelial inflammation via the reactive oxygen species (ROS)–nucleotide‐binding, oligomerization domain–like receptor family, pyrin domain containing 3 (NLRP3)–caspase‐1–interleukin 1β (IL‐1β) pathway

Abstract: Background Allergic rhinitis AR is an increasing challenge to public health worldwide Exposure to environmental black carbon BC is associated with increased risk of allergic rhinitis but the molecular mechanisms underlying its toxicity have not been fully elucidated The aims of the present study were therefore to determine the effect of BC on the expression of interleukin β IL-β and to investigate the mechanism underlying BC-induced IL-β production in pollen-sensitized human nasal epithelial cells hNECs Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…This suggested that the development of AR could be dependent on the ROS increase, which in turn, led to the activation of NLRP3 inflammasome and increased the level of IL-1b in nasal epithelial cells (27). Consistent results were obtained by Li et al on human nasal mucosa samples (hNEC) (28) showing that an ozone-oxidised black carbon (BC) and pollen exposure led to oxidative stress by increasing the level of ROS production. Consequently, it increased the mRNA and protein levels of NLRP3 and IL-1b.…”
Section: Allergic Rhinitis -Link With Nlrp3 and Il-1bsupporting
confidence: 62%
“…This suggested that the development of AR could be dependent on the ROS increase, which in turn, led to the activation of NLRP3 inflammasome and increased the level of IL-1b in nasal epithelial cells (27). Consistent results were obtained by Li et al on human nasal mucosa samples (hNEC) (28) showing that an ozone-oxidised black carbon (BC) and pollen exposure led to oxidative stress by increasing the level of ROS production. Consequently, it increased the mRNA and protein levels of NLRP3 and IL-1b.…”
Section: Allergic Rhinitis -Link With Nlrp3 and Il-1bsupporting
confidence: 62%
“…Li et al reported that black carbon and pollen were associated with oxidative stress in the nasal mucosa and the combination of these two could even aggregate the inflammation. 28 In fact, NO 2 is a relatively weak oxidant, while O 3 is a strong oxidant. In mice and rat models, ozone induced nasal type 2 immunity and aggravated eosinophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk was expressed as an odds ratio (OR) per one interquartile range (IQR, Q3 minus Q1) of each air pollutant. During the study period, the IQR levels of air pollutants were 2 (Q1-Q3;2-4) μg/m 3 for sulfur dioxide (SO 2 ), 16 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) μg/m 3 for nitrogen dioxide (NO 2 ), 44 (60-104) μg/m 3 for ozone (O 3 ), 54 (32-86) μg/m 3 for particulate matter ≤10 μm in aerodynamic diameter (PM 10 ), 40(15-55) μg/m 3 for particulate matter ≤2.5 μm in aerodynamic diameter (PM 2.5 ), and 0.44 (0.4-0.84) μg/m 3 for carbon monoxide (CO).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[38][39][40] This may be due to the effect of PM 10 to AR in terms of "nonspecific nasal hyperreactivity" rather than allergic sensitization; it has been proposed that PM 10 could exacerbate the inflammatory response of the nasal epithelial cells by increasing the oxidate distress in patients with AR when exposed to an aeroallergen. 11,41 The more specific mechanism of action by which air pollutants have effects on inflammatory sinonasal diseases including AR needs further investigation and research.…”
Section: Discussionmentioning
confidence: 99%